Climate change, mobility and violent conflict: a typology of interlinked pathways - Savelli, Adam; Schapendonk, Frans; Dutta Gupta, Tanaya; Pacillo, Grazia; Läderach, Peter R.D. (University of Liverpool, 2023)
Despite increased attention toward the links between climate, human mobility and conflict, the pathways through which resulting human insecurity may lead to violence are poorly understood. Although there is no inherent link between climate-related mobility and conflict, a coherent understanding of the triple nexus is needed to address the impact of intersecting crises on millions of lives and livelihoods. To achieve this, an in-depth literature review is employed to identify and explore four pathways that connect climate, human mobility and violent conflict: conflict as a result of climate-related disaster displacement, conflict as a result of scarcity-related mobility, conflict as a result of abundance-related migration, and conflict as a result of pre-existing tensions and migratory patterns interacting with climate change and/or variability. Finally, recommendations are made to guide research, policies and programming aiming to sever the link between climate-related mobility and conflict, where it may exist.